Association between weight-adjusted waist index and overactive bladder: a cross-sectional study based on 2009–2018 NHANES - Hui, Zeng; Zewu, Zhu; Yang, Li; Yu, Cui (Frontiers in Nutrition, 2024)
The weight-adjusted waist index (WWI) is a novel obesity indicator that appears to outperform the body mass index (BMI) and waist circumference (WC) in assessing both overweight and obesity. Studies have demonstrated the relationship between obesity and overactive bladder (OAB). The purpose of this study is to examine the correlation between WWI and OAB.Methods: This research utilizes data from the National Health and Nutrition Examination Survey (NHANES) collected between 2009 and 2018. Each participant's WWI was calculated as their WC in centimeters by the square root of weight in kilograms. The Overactive Bladder Symptom Score (OABSS) questionnaire is used to determine whether a participant has OAB.Multivariate logistic regression and generalized additive model analysis were employed to investigate the relationship between WWI and OAB. We used smoothing curve fitting to explore nonlinear relationships. Additionally, subgroup analysis and interaction tests are conducted.In this cross-sectional study involving 35,950 subjects, we found that individuals with a higher WWI have a higher risk of OAB (OR =1.41, 95% CI:1.02-1.74). Subgroup analysis and interaction testing showed that the relationship between WWI and OAB is consistent across various population characteristics.Smoothing curve fitting reveals a positive nonlinear relationship between WWI and OAB. Furthermore, the association between WWI and OAB is stronger than that of other obesity-related indicators.Conclusions: WWI may be able to predict the incidence of OAB and that WWI-based obesity management may help to reduce the risk of OAB.